Simulation & performance of space time frequency by using turbo codes: article / Ismail Ibrahim - Ibrahim, Ismail
This peper highlights the simulation using space time frequency coding (STFC) in order to identify the performance capability of turbo code with using a queternary phase shift keying (QPSK) modulation technique generally' turbo code es encoder is functioning to convert the input signal become into e binary form before the modulation happens.